Overall Survival with Adjuvant Pembrolizumab in Renal-Cell Carcinoma - Choueiri, Toni K; Tomczak, Piotr; Park, Se Hoon; Venugopal, Balaji; Ferguson, Tom; Symeonides, Stefan N; Hajek, Jaroslav; Chang, Yen-Hwa; Lee, Jae-Lyun; Sarwar, Naveed; Haas, Naomi B; Gurney, Howard; et al. (The New England journal of medicine, 2024)
BACKGROUND: Adjuvant pembrolizumab therapy after surgery for renal-cell carcinoma was approved on the basis of a significant improvement in disease-free survival in the KEYNOTE-564 trial. Whether the results regarding overall survival from the third prespecified interim analysis of the trial would also favor pembrolizumab was uncertain. METHODS: In this phase 3, double-blind, placebo-controlled trial, we randomly assigned (in a 1:1 ratio) participants with clear-cell renal-cell carcinoma who had an increased risk of recurrence after surgery to receive pembrolizumab (at a dose of 200 mg) or placebo every 3 weeks for up to 17 cycles (approximately 1 year) or until recurrence, the occurrence of unacceptable toxic effects, or withdrawal of consent. A significant improvement in disease-free survival according to investigator assessment (the primary end point) was shown previously. Overall survival was the key secondary end point. Safety was a secondary end point. RESULTS: A total of 496 participants were assigned to receive pembrolizumab and 498 to receive placebo. As of September 15, 2023, the median follow-up was 57.2 months. The disease-free survival benefit was consistent with that in previous analyses (hazard ratio for recurrence or death, 0.72; 95% confidence interval [CI], 0.59 to 0.87). A significant improvement in overall survival was observed with pembrolizumab as compared with placebo (hazard ratio for death, 0.62; 95% CI, 0.44 to 0.87; P = 0.005). The estimated overall survival at 48 months was 91.2% in the pembrolizumab group, as compared with 86.0% in the placebo group; the benefit was consistent across key subgroups. Pembrolizumab was associated with a higher incidence of serious adverse events of any cause (20.7%, vs. 11.5% with placebo) and of grade 3 or 4 adverse events related to pembrolizumab or placebo (18.6% vs. 1.2%). No deaths were attributed to pembrolizumab therapy. CONCLUSIONS: Adjuvant pembrolizumab was associated with a significant and clinically meaningful improvement in overall survival, as compared with placebo, among participants with clear-cell renal-cell carcinoma at increased risk for recurrence after surgery. (Funded by Merck Sharp and Dohme, a subsidiary of Merck; KEYNOTE-564 ClinicalTrials.gov number, NCT03142334.).
Keywords: kombinovaná terapie; analýza přežití; nádory ledvin; Disease-Free Survival; Combined Modality Therapy; Antineoplastic Agents, Immunological; karcinom z renálních buněk; Kidney Neoplasms; protinádorové látky imunologicky aktivní; Survival Analysis; dvojitá slepá metoda; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Adjuvants, Immunologic; lidé; Humans; adjuvancia imunologická; Carcinoma, Renal Cell; Double-Blind Method; přežití bez známek nemoci